Using a methodology for material procurement in a construction company in the town of Campos dos Goytacazes - Ferreira, Jean Crispim; Carvalho, Rogério Atem de; Costa, Helder Gomes (Revista Gestão da Produção Operações e Sistemas, 2008)
The sector of construction in Brazil has a great economic importance, with effective participation in both wages and number of employees in the Brazilian GIP. This fact reflects the necessity of a better attention to the sector, aiming to improve the infrastructure of the country and at the same time to generate better incomes and jobs, having as consequence the increase of the GIP of the country. In such a way, the present work aims to present a case study with application of the methodology proposed by Carvalho (2001), directed to a civil construction company of the city of Campos dos Goytacazes, aiming to illustrate a way of improvement for this economic sector. The methodology aims to provide tools to support the decision process in the supply chain, searching for an optimal set of supply contracts. The focus of the methodology is the analysis of the relation of each supplier and each product, forming pairs supplier / product, that are the decision alternatives for the models, searching the reduction of the costs of the acquired material. Therefore, information models are presented to give support in the decision making. Keywords: Construction Industry, Optimization, Supply Chain Management, Supplier Relationship Management.